Managing information technology projects in the public sector. - Cats-Baril, William; Thompson, Ronald L. (Public Administration Review)
A framework to address the requirements of managing large scale information technology (IT) projects in the public sector is presented. The differences between public and private organizations are examined, and recent trends in human resource management systems (HRMS) are outlined. A case study of the State of Vermont's HRMS is provided, detailing how concerns expressed in 1987 by the director of payroll for Vermont over the existing payroll system led to a major systems project being undertaken, how the project was two years late and more than $1 million over budget, and how, by early 1995, the system was still encountering some problems. This case is used to illustrate many of the pitfalls of public sector management of IT projects. Finally, modifications to private sector management techniques are proposed, and lessons that can be learned from the HRMS experience are identified.